Altered glial plasticity in animal models for mood disorders - Czéh, Boldizsár; Fuchs, Eberhard; Flügge, Gabriele (Current drug targets, 2013)
Numerous clinical evidences support the notion that glial changes in fronto-limbic brain areas could contribute to the pathophysiology of mood disorders. Glial alterations have been reported not only in patients, but also in various kinds of animal models for depression. Molecular and cellular data suggest that all the major classes of glial cells are affected in these conditions, including astrocytes, oligodendrocytes, NG2-positive cells and microglia. The aim of this review was to summarize the currently available experimental results demonstrating alterations in glial morphology and functioning in animal models for mood disorders. Better understanding of these glial changes affecting neuronal activity could help us to identify novel targets for the development of antidepressant drugs.